Cardiac Autonomic Modulation in Domestic Cats with Obstructive Lower Urinary Tract Disease - Tarazona Molina, Mary Marlene [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Cruz-Aleixo, Amanda Sarita [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Valença Corrêa, Jaqueline [UNESP]; Cardia de Melo, Jessica [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (MDPI, 2024)
Obstructive feline lower urinary tract disease (OFLUTD) is the most common complication of the urinary system, as metabolic and electrolyte changes can alter the functioning of the autonomic nervous system (ANS). The objective of this study was to describe the indices of heart rate variability (HRV) and their correlations with the observed alterations in Systolic Blood Pressure (SBP) and electrocardiographic, biochemical, and haemogasometric indices in cats diagnosed with OFLUTD. Sixty-five male cats up to 10 years of age were divided into two groups. The control group (CG) was composed of 25 healthy cats, and the obstructed group (OG) consisted of 40 cats with OFLUTD. The OG was evaluated by electrocardiography and blood pressure at four different time points. In the CG, electrocardiographic evaluation and SBP measurement were performed. A comparison of the HRV between the CG and OG (M0) revealed differences in the SDNN (standard deviation of all normal RR-NN) parameters (sympathetic and parasympathetic tone) and in the rMSSD (parasympathetic tone); there was a difference in the SBP, which was greater in the CG. There were higher rates in the CG. The HF and HR were greater in OG. The HRV serves as a preventive tool and predicts the severity of OFLUTD in patients due to an imbalance in the ANS.
Keywords: autonomic nervous system; cardiology; obstruction; potassium